A reference architecture for big data solutions - introducing a model to perform predictive analytics using big data technology. (2015) - Geerdink, Bas
With big data technology and predictive analytics techniques, organisations can now register, combine, process and analyse data to answer questions that were unsolvable a few years ago. This paper introduces a solution reference architecture that gives guidance to organisations that want to innovate using big data technology and predictive analytics techniques for improving their performance. The reference architecture is the result of one iteration of Hevner's framework for designing information systems artefacts.